2021
DOI: 10.1093/ckj/sfab244
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids and mycophenolic acid analogues in immunoglobulin A nephropathy with progressive decline in kidney function

Abstract: Background A randomized controlled trial (RCT) demonstrated a beneficial effect of corticosteroids (CS) plus cyclophosphamide followed by azathioprine in progressive IgA nephropathy (IgAN). Although treatment with CS and mycophenolic acid analogs (MPAA) remains controversial in IgAN, there is no information about their effect in progressive IgAN. Methods Patients with progressive IgAN, defined by a decrease in estimated glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A recently published Argentinian-Spanish retrospective study assessed the impact of steroids plus mycophenolate in a cohort of 25 patients with progressive IgAN [54]. Progressive IgAN was defined by a decrease in eGFR of at least 10 mL/min in the 12 months prior to the start of treatment and proteinuria ≥0.75 g/day despite maximum tolerated doses of RAS blockade, and hematuria (≥5 red blood cells per high power field) at the beginning of treatment.…”
Section: Treatment and Crescents In Iganmentioning
confidence: 99%
“…A recently published Argentinian-Spanish retrospective study assessed the impact of steroids plus mycophenolate in a cohort of 25 patients with progressive IgAN [54]. Progressive IgAN was defined by a decrease in eGFR of at least 10 mL/min in the 12 months prior to the start of treatment and proteinuria ≥0.75 g/day despite maximum tolerated doses of RAS blockade, and hematuria (≥5 red blood cells per high power field) at the beginning of treatment.…”
Section: Treatment and Crescents In Iganmentioning
confidence: 99%
“…Simultaneously, the results of a prospective study in Hong Kong showed that for IgAN patients with moderate renal insufficiency and proteinuria >1.8 g/d, the use of MMF resulted in a significant decrease in urinary protein and a higher 6-year renal survival rate ( Tang et al, 2005 ). Not long ago, scholars reported that corticosteroids + MMF is an effective treatment in IgAN patients with a sustained decline in kidney function accompanied by persistent proteinuria and haematuria despite optimized conservative treatment ( Huerta et al, 2022 ). However, foreign prospective studies have not found that MMF has a renoprotective effect on IgAN ( Zheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether patients with proliferative lesions such as E1 and C1 should be initiated on immunosuppression immediately after diagnosis irrespective of their proteinuria levels to prevent fibrosis or one should wait to assess response to RAAS blockade for 3 months, which may actually increase the risk of progressive chronic disease remains debatable. 16 , 17 Again, whether patients with persistent proteinuria >1 g/d due to secondary glomerulosclerosis and hyperfiltration should receive immunosuppression as per KDIGO guidelines or continued on optimized nephroprotective supportive therapy also remains controversial and needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The use of long-term immunosuppression (low dose, maintenance) to prevent relapsing proteinuria and progression of disease was not investigated, which is also a gap not addressed by the KDIGO guidelines. The use of the International IgAN network tool 16 to prognosticate patients was not assessed in our survey. Most of the respondents were mainly from Asia and South America, and other regions were underrepresented.…”
Section: Discussionmentioning
confidence: 99%